Groundwater Resources Estimation in the Middle of Randublatung Groundwater Basin Based on Geoelectrical Investigation. Issue 1 (December 2021) - Setyaningsih, D L; Setyawan, K; Putra, D P E; Salahuddin,
Abstract: The high groundwater use in the Randublatung Groundwater Basin area relates to groundwater abstraction for agriculture. Therefore, a question arises on how much groundwater resources in this area may support agricultural groundwater usage. This research has the objective to quantify the groundwater resources in this area. This research conducts a geoelectrical investigation to identify the aquifer's lithology and observe the groundwater level. The research reveals that resistivity values of subsurface rock layers in the research area range from 0.13 to 124.86 Ωm. The aquifer layer consisted of two aquifer systems, with the hydraulic conductivity varies of the aquifer layer is 0.0001 cm/s until 0.01 cm/s. The aquifer layers estimated to be found at depths vary 5 – 90 m from the ground with thickness range from 10 to 70 m. Meanwhile, the aquiclude layers consisted of clay, silty clay, and sandy clay was estimated to be found at depths varies 0 – 50 m from the ground with thickness varies from 5 to 65 m. by combining those data with a hydraulic gradient of groundwater flow, the dynamic groundwater resources in the research area is estimated between 50 m 3 /day and 4, 691 m 3 /day.